2012
DOI: 10.1148/radiol.11100878
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodules: Growth Rate Assessment in Patients by Using Serial CT and Three-dimensional Volumetry

Abstract: A normative model derived from the variability of growth rates of nodules that were stable for an average of 6.4 years may enable identification of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 49 publications
1
66
0
2
Order By: Relevance
“…It is a common imaging artefact when a limited spatial resolution is used to perform CT scans and, consequently, different tissues are included in the same pixel/voxel [50, 52,[65][66][67][68][69]. When attenuation value is not sufficient to distinguish nodule borders, segmentation errors could occur, as in the case of nonspherical or irregular lesions [41,65,68,[70][71][72], as well as in juxtavascular or juxtapleural ones [72][73][74]. Reduced nodule attenuation, as in the case of SSNs, could also affect nodule segmentation when using the commonest threshold density technique, because of the low attenuation difference between nodule borders and the surrounding parenchyma [50].…”
Section: Factors Influencing Nodule Measurement Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common imaging artefact when a limited spatial resolution is used to perform CT scans and, consequently, different tissues are included in the same pixel/voxel [50, 52,[65][66][67][68][69]. When attenuation value is not sufficient to distinguish nodule borders, segmentation errors could occur, as in the case of nonspherical or irregular lesions [41,65,68,[70][71][72], as well as in juxtavascular or juxtapleural ones [72][73][74]. Reduced nodule attenuation, as in the case of SSNs, could also affect nodule segmentation when using the commonest threshold density technique, because of the low attenuation difference between nodule borders and the surrounding parenchyma [50].…”
Section: Factors Influencing Nodule Measurement Variationsmentioning
confidence: 99%
“…Intuitively, the direct assessment of nodule volume and VDT provides an accurate estimation of nodule growth [51]. Combined with lower uncertainty of measurements, the 3D method allows detection of changes even within a shorter period of time, resulting in a higher sensitivity of volume-based techniques in growth evaluation [26,73] (figure 3). Estimations of nodule growth rates obtained from automated 3D volumetric measurements showed a good correlation with 2D diameter measurements, with a greater divergence for irregular lesions [70].…”
Section: Effect Of Measurement Variations On Nodule Growthmentioning
confidence: 99%
“…They are from a set of lung nodules used in a previous study in which an average CT follow-up period of 6.4 years was employed to analyze the precision of growth rate measurements [14]. The mean linear dimension of nodules in our set is 5.4 mm±3.0, with a range from 1.9 to 28.5 mm.…”
Section: Patient-based Comparisonmentioning
confidence: 99%
“…Therefore, computer-assisted methods of lung nodule characterization have been investigated. Assessment of lung nodules thus far has focused primarily on growth rate, attenuation, shape, texture, and the use of neural networks [13][14][15][16][17][18][19]. Assessing change in a nodule entails evaluating not only the lesion's growth rate but also any alterations in morphology.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the texture at the edge of the nodules is critical in distinguishing malignant from benign nodules (Wang et al, 2010). Curvelet transformation (Guo et al, 2012), which is ideally suited to the analysis of two-dimensional (2D) images, has proven to be particularly effective at detecting image activity along curves instead of radial directions when compared with other transforms (Ko et al, 2012). It has been used in the analysis of medical images (Dettori and Semler, 2007;Eltoukhy et al, 2010;Meselhy Eltoukhy et al, 2010), such as CT scans, endoscope images, X-rays, etc.…”
mentioning
confidence: 99%